Enhancing anti-tumor immunity through co-blocking PD-L1 and TIGIT by facilitating tumor-directed responses and additional VEGF inhibition - Zhu, Xi; Cui, Xiaopei; Yu, Haijia; Xu, Jingen; Chen, Xiaofang; Ren, Xiaochen; Wei, Xiaoyue; Chen, Shi; Wang, Yangtin; Fei, Liyang; Xie, Bin; Li, Mingwei; et al. (Frontiers in Immunology, 2026)
Combination therapy targeting the PD-1/PD-L1 and TIGIT pathways has been explored to enhance the efficacy of current immunotherapies. In this study, we investigated strategies to further potentiate the co-blockade of PD-L1 and TIGIT for cancer immunotherapy. Firstly, we demonstrated that the bispecific antibody (HB0036) for PD-L1 and TIGIT co-blockade induced a greater T-cell proliferative response in vitro compared to the combined administration of the parental antibodies. This response was associated with CD226 upregulation and PD-1 downregulation. HB0036 significantly enriched the TIGIT antibody at PD-L1+ tumors and achieved improved tumor control with favorable immunological characteristics in both syngeneic and xenograft tumor models. Secondly, we showed that tumor control by co-targeting PD-L1 and TIGIT can be further enhanced by additionally blocking VEGF, a key player in tumorigenesis and tumor angiogenesis, in preclinical studies. Lastly, considering the heterogeneity of tumors, we analyzed how the expression patterns of PD-L1 and CD155 influence T cell responses. We also examined the spatial distribution of PD-L1 and CD155, along with related immunological parameters from patient samples, to assess the potential of PD-L1 and TIGIT co-blockade in diverse tumor contexts.